Vaccine and Cell-based Therapeutic Approaches in Acute Myeloid Leukemia - Agrawal, Vaibhav; Gbolahan, Olumide B.; Stahl, Maximilian; Zeidan, Amer M.; Zaid, Mohammad A.; Farag, Sherif S.; Konig, Heiko (Current Cancer Drug Targets, 2020)
Over the past decade, our increased understanding of the interactions between the immune system and cancer cells has led to paradigm shifts in the clinical management of solid and hematologic malignancies. The incorporation of immune-targeted strategies into the treatment landscape of acute myeloid leukemia (AML), however, has been challenging. While this is in part due to the inability of the immune system to mount an effective tumor-specific immunogenic response against the heterogeneous nature of AML, the decreased immunogenicity of AML cells also represents a major obstacle in the effort to design effective immunotherapeutic strategies. In fact, AML cells have been shown to employ sophisticated escape mechanisms to evade elimination, such as direct immunosuppression of natural killer cells and decreased surface receptor expression leading to impaired recognition by the immune system. Yet, cellular and humoral immune reactions against tumor-associated antigens (TAA) of acute leukemia cells have been reported and the success of allogeneic stem cell transplantation and monoclonal antibodies in the treatment of AML clearly provides proof that an immunotherapeutic approach is feasible in the management of this disease. This review discusses the recent progress and persisting challenges in cellular immunotherapy for patients with AML.
Keywords: NK cell